Impact of Undiagnosed Hypertension In Patients Presenting With Stroke: Comparison With Patients Having Diagnosed Hypertension - Mahmood, Muhammad Ahsan; Salman Saleem; Soban Ahmed Tariq; Ahmad Sagheer Cheema; Amar Anwar; Iqra Anwar (Pakistan Armed Forces Medical Journal, 2024)
Objectives: To compare morbidity and mortality among stroke patients with undiagnosed hypertension vs those with pre-existing, diagnosed hypertension. Study Design: Cross-sectional study. Place and Duration of Study: Pak Emirates Military Hospital, Rawalpindi Pakistan from December 2022 to May 2023. Methodology: A total of 86 patients fulfilling the inclusion criteria were included in the study. Detailed history was obtained to assess for hypertension i.e., undiagnosed hypertension (group A) or pre-existing, diagnosed hypertension (group B). Stroke outcomes including type of stroke, in-hospital mortality and 30-day disability were compared between groups using Chi-square and Mann-Whittney U-test. Results: Mean age of patients was 55.18±11.31 years. There were 57(66.28%) male and 29(33.72%) female patients. Frequency of “undiagnosed hypertension (HTN)” was 26(30.23%) while of “pre-existing hypertension (HTN)” it was 60(69.77%). Patients with “undiagnosed hypertension” were found to have significantly higher frequency of hemorrhagic stroke (p<0.001), in-hospital mortality (p = 0.001) and 30-days disability score (p<0.001). Conclusion: Frequency of undiagnosed hypertension in stroke patients was 30.23% and is associated with poor outcomes in term of morbidity and mortality in stroke patients as compared to those having pre-existing, diagnosed hypertension.